Atlas of Dentomaxillofacial Anatomical Imaging - Delantoni, Antigoni; Orhan, Kaan.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This atlas is a detailed and complete guide on imaging of the dentomaxillofacial region, a region of high interest to a wide range of specialists. A large number of injuries and patient$1 (Bs treatment involve the facial skeleton. Enriched by radiographic images and illustrations, this book explores the anatomy of this region presenting its imaging characteristics through the most commonly available techniques (MDCT, CBCT, MRI and US). In addition, two special chapters on angiography and micro-CT expand the limits of dentomaxillofacial imaging. This comprehensive book will be an invaluable tool for radiologists, dentists, surgeons and ENT specialists in their training and daily practice.s
Chapter 1) Introduction to Dentomaxillofacial Imaging -- Chapter 2) Basic Principles of Intraoral Radiography -- Chapter 3) Intraoral Radiographic Anatomy -- Chapter 4Basic Principles of Panoramic Radiography -- Chapter 5) Panoramic Radiographic Anatomy -- Chapter 6) Cephalometric Radiography -- Chapter 7) Basic Principles of Computer Tomography (MDCT/CBCT). The Use of MDCT and CBCT in Dentomaxillofacial Imaging -- Chapter 8) CBCT Anatomical Imaging -- Chapter 9) MDCT Soft Tissue Anatomy -- Chapter 10) Dentomaxillofacial Ultrasonography: Basic Principles and Radiographic Anatomy -- Chapter 11) Basics of Magnetic Resonance Imaging (MRI) -- Chapter 12) MRI Anatomy -- Chapter 13) Principles of Maxillofacial Angiography -- Chapter 14) Imaging of the Most Common Dental Pathologies -- Chapter 15) Micro CT. .
Keywords: Radiology; Dentistry; Surgery; Radiology; Dentistry; Surgery; Stomatognathic System -- diagnostic imaging; Stomatognathic Diseases -- diagnostic imaging; Radiography -- methods